2021
DOI: 10.3389/ijph.2021.1604277
|View full text |Cite
|
Sign up to set email alerts
|

Facemask Usage Among People With Primary Ciliary Dyskinesia During the COVID-19 Pandemic: A Participatory Project

Abstract: Objectives: Primary ciliary dyskinesia (PCD) is a rare genetic disease that causes recurrent respiratory infections. People with PCD may be at high risk of severe COVID-19 and protection against SARS-CoV-2 is therefore important. We studied facemask usage and problems reported in relation with their use among people with PCD.Methods: We used data from COVID-PCD, an international observational cohort study. A questionnaire was e-mailed to participants in October 2020 that asked about facemask usage.Results: In … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 37 publications
0
13
1
Order By: Relevance
“…In our study, we did not ask whether participants kept social distancing when going out or seeing friends and family, but around 20% said that they did shake hands with people more often after getting vaccinated. This is in contrast to previous studies that found that people with PCD are very careful in protecting themselves against COVID-19 by avoiding public places and always wearing facemasks [44].…”
Section: Strengths and Limitationscontrasting
confidence: 93%
“…In our study, we did not ask whether participants kept social distancing when going out or seeing friends and family, but around 20% said that they did shake hands with people more often after getting vaccinated. This is in contrast to previous studies that found that people with PCD are very careful in protecting themselves against COVID-19 by avoiding public places and always wearing facemasks [44].…”
Section: Strengths and Limitationscontrasting
confidence: 93%
“…Because recruitment started in early 2020, these results are possibly affected by the COVID-19 pandemic. Based on anecdotal evidence, patients with PCD experienced fewer infections due to careful shielding, which possibly led to decreased prevalence of ear problems . As the cohort continues to be followed up longitudinally, it will be important to study possible changes in symptoms and signs coinciding with relaxing pandemic measures.…”
Section: Discussionmentioning
confidence: 99%
“…Comparing incidence rate of reported SARS-CoV-2 in our study with wholecountry incidence rates should however be done with caution due to differences in case definitions and methods for calculating follow-up time. The low incidence in our study population may be because people with PCD exhibited particular caution by reducing social contact, wearing masks in public, and getting vaccinated against COVID-19 18,23,24 . The extraordinary effort from PCD support groups taken to inform and encourage people with PCD throughout the pandemic may also have contributed to the low incidence.…”
Section: Interpretation and Clinical Implicationsmentioning
confidence: 81%
“…In December 2021 after 80 weeks of follow-up, we reduced the frequency of follow-up questionnaires to once every four weeks. Participants also received two extra questionnaires which studied specific questions in detail; one focused on use of face masks and one on COVID-19 is the author/funder, who has granted medRxiv a license to display the preprint in (which was not certified by peer review) vaccinations 23,24 . The present paper includes all study participants who completed the baseline questionnaire.…”
Section: Study Procedures and Questionnairesmentioning
confidence: 99%